PENGARUH PENERAPAN STRATEGI PQ4R MENGGUNAKAN MEDIA FLIP BOOK TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD DI ERA PANDEMI - Lilis Sumaryani; Rusijono Rusijono; Suhanadji Suhanadji (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
This research aims to apply the PQ4R strategy with social studies flip book media to 5th grade students of SDN Geluran 1 in online learning. This is done in order to improve student learning outcomes during online learning that is less interactive due to the Covid-19 pandemic. Data were obtained from class 5 SDN Geluran 1, Taman District, Sidoarjo Regency. This research method uses pretest-posttest control group design. The results of this study are as follows: (1) Learning activities with the application of PQ4R strategy through flip book media, there are two activities, namely teacher activities, the results of which are 86.25% can be categorized as very good and for student activities, 84% are obtained in the very good category. (2) Student responses to the implementation of the PQ4R strategy through flip book media on social studies learning outcomes in class V, there is a percentage of 73% which can be categorized as good. (3) The application of the PQ4R strategy through flip book media on social studies learning outcomes in grade 5 in a similar sample, namely the experimental group there is thitung > ttabel or 33,609 > 1,708. While the learning outcomes with different types of data, namely the experimental group and the control group obtained thitung of 2,262 and ttabel of 2,000, then thitung > ttabel. In other words, Ha is accepted and Ho is rejected. Thus, it can be concluded that the application of PQ4R using flip book media has a very good effect on learning outcomes for social studies subjects for grade 5 students at SDN Geluran 1, Taman Subdistrict, Sidoarjo Regency. Keyword : Flip Book Media, PQ4R Strategy, Learning Outcomes, and Online Learning